2022
DOI: 10.1186/s40359-022-00910-9
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarette use and intentions related to psychological distress among cigarette, e-cigarette, and cannabis vape users during the start of the COVID-19 pandemic

Abstract: Background This study examines associations between psychological distress, intentions to use e-cigarettes, and cigarette smoking, e-cigarette use, and cannabis consumption through e-cigarette use among a diverse sample of U.S. young adults. Procedures Young adults (N = 314; 72.5% female) were recruited to complete an online survey during the first few months of the COVID-19 pandemic. Results Associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Given that e-cigarette use may be a coping mechanism for those dealing with psychological distress, additional social and emotional support might be needed to reduce and abstain from e-cigarette use ( Xie et al, 2022 ). These factors, in addition to gender, need to be considered when planning for social support-based digital vaping cessation programs since prior studies have found that females report higher psychological distress, compared to males ( Cabral, 2022 ) and that the impacts that emotional and social support have on treatment for psychological distress differ by gender ( Martínez-Hernáez et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that e-cigarette use may be a coping mechanism for those dealing with psychological distress, additional social and emotional support might be needed to reduce and abstain from e-cigarette use ( Xie et al, 2022 ). These factors, in addition to gender, need to be considered when planning for social support-based digital vaping cessation programs since prior studies have found that females report higher psychological distress, compared to males ( Cabral, 2022 ) and that the impacts that emotional and social support have on treatment for psychological distress differ by gender ( Martínez-Hernáez et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This definition of intention to use e-cigarettes was also used in previous studies. [27][28][29] Independent variables. We also used other independent variable groups, including:…”
Section: Study Variablesmentioning
confidence: 99%
“…This health crisis, marked by an intensified focus on personal health and safety, may have contributed to changes in attitudes and behaviors relating to e-cigarette use . Psychological stress and isolation that may have arisen from lockdown measures also may have prompted some individuals to increasingly depend on e-cigarettes and other tobacco products as a coping mechanism . In addition, the COVID-19 pandemic disrupted the conduct of surveys, especially those that relied on in-person data collection.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Psychological stress and isolation that may have arisen from lockdown measures also may have prompted some individuals to increasingly depend on e-cigarettes and other tobacco products as a coping mechanism. 14 , 15 In addition, the COVID-19 pandemic disrupted the conduct of surveys, especially those that relied on in-person data collection. As a result, surveys such as the NHIS transitioned from in-person to online interviews.…”
Section: Introductionmentioning
confidence: 99%